Georgie & Mandy's first marriage. The complete first season [videorecording (DVD)]. - Jordan, Montana; Osment, Emily; Jones, Rachel Bay (Warner Bros., 2025)
Georgie and Mandy raise their young family in Texas while navigating the challenges of adulthood, parenting, and marriage.